Factors Affecting Late-Life Conversion - Arn, Charles (Christian education journal, 2008)
Christian conversion rates are highest in early and middle age, then drop dramatically after age 50. An analysis of senior adult conversions identifies variables that can increase the effectiveness of evangelization approaches with older adults.